2016
DOI: 10.1007/s10815-016-0764-7
|View full text |Cite
|
Sign up to set email alerts
|

Micro-dose hCG as luteal phase support without exogenous progesterone administration: mathematical modelling of the hCG concentration in circulation and initial clinical experience

Abstract: For the last two decades, exogenous progesterone administration has been used as luteal phase support (LPS) in connection with controlled ovarian stimulation combined with use of the human chorionic gonadotropin (hCG) trigger for the final maturation of follicles. The introduction of the GnRHa trigger to induce ovulation showed that exogenous progesterone administration without hCG supplementation was insufficient to obtain satisfactory pregnancy rates. This has prompted development of alternative strategies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…With these regimens, the concentrations of LH/hCG achieved during the luteal phase often reached levels fiveto tenfold higher than those seen in the normal menstrual cycle. In today's standards, exogenous hCG used at these doses causes far too strong an LPS and significantly enhances the risk of OHSS (48). This has been highlighted in a Cochrane review, which bluntly states, ''We found that hCG, or hCG plus progesterone, was associated with a higher risk of OHSS.…”
Section: Hcg For Luteal Phase Supportmentioning
confidence: 96%
See 3 more Smart Citations
“…With these regimens, the concentrations of LH/hCG achieved during the luteal phase often reached levels fiveto tenfold higher than those seen in the normal menstrual cycle. In today's standards, exogenous hCG used at these doses causes far too strong an LPS and significantly enhances the risk of OHSS (48). This has been highlighted in a Cochrane review, which bluntly states, ''We found that hCG, or hCG plus progesterone, was associated with a higher risk of OHSS.…”
Section: Hcg For Luteal Phase Supportmentioning
confidence: 96%
“…Indeed, this approach allowed abandoning the large boluses of hCG used for triggering ovulation, but required a supplementary dose of 1,500 IU hCG to sustain sufficient endogenous P production and maintain similar pregnancy rates (49)(50)(51). This concept was further developed to include daily microdoses of hCG of only 100-150 IU throughout the luteal phase without using any exogenous P preparation (48,52). Microdoses of hCG administered to women undergoing OS with the use of agonist trigger for final maturation of oocytes led to hCG concentrations that do not exceed physiologic levels (i.e., 5-10 IU/L).…”
Section: Hcg For Luteal Phase Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Andersen et al [16,17] showed that a daily dose of hCG (125 IU) starting on the day of oocyte retrieval (without exogenous P) results in very high mid-luteal P. Daily hCG was stopped 12 days after embryo transfer.…”
Section: Luteal Support Based On Repeated Lh/hcg Dosingmentioning
confidence: 99%